Cardiac myxomas: an analysis of 39 patients - Toktaş, Faruk; Yavuz, Şenol; Özsin, Kadir Kaan; Sanrı, Umut Serhat; Türk, Tamer; Göncü, Mehmet Tuğrul (The European Research Journal, 2017)
Objectives. Myxomas are the most common benign primary heart tumors. They have serious complications including intracardiac blood flow obstruction and embolic events. The aim of the study was to assess our experiences related to patients undergoing surgical resection for cardiac myxomas.Methods. The medical records of 39 patients, aged 16 to 76 years (mean, 47.5 years), who were operated on for primary cardiac myxomas between January 1994 and December 2016 at our clinic were retrospectively evaluated. Demographic, clinical, operative and postoperative data were obtained from these hospital medical records. Cardiac myxomas were diagnosed by transthoracic echocardiography. Preoperative coronary angiography was performed in patients over 40 years of age and those with symptoms of coronary disease. In routine follow-up after discharge the patients were checked by echocardiography. Long-term cumulative survival was analyzed using the Kaplan-Meier method.Results. There was no in-hospital mortality. The majority (61.5%) of patients were female. The most common encountered localization of myxoma was the left atrium (76.9%), and the classic posterior approach from interatrial groove was preferred in 32 (82.1%) patients. Mean follow-up was 6.05 ± 3.75 years (range, 1-10 years). Five (12.8%) patients were lost on long-term follow-up. Kaplan-Meier curves, cumulative proportion surviving of patients at 1-, 2-, 5-, and 10-year were 97.4%, 91.7%, 84.7%, and 84.7%, respectively. No hospital mortality was observed in any of the patients. There was no recurrence in our series. Conclusions. Myxoma is the disease that can lead to complications such as embolic events and intracardiac blood flow obstruction. It can be excised with a low rate of morbidity and mortality. Surgical resection should be performed promptly after diagnosis in order to prevent potential complications.